Organisational justice - organisational citizenship behaviour relationship: the mediating role of job satisfaction and leader - member exchange in the manufacturing sector in Malaysia - Hooi, Lai Wan (Kulliyyah of Economics and Management Sciences, International Islamic University Malysia, 2012)
This study explores the mediating roles of job satisfaction and leader-member exchange in the justice-citizenship relationship in the manufacturing sector in Malaysia. Specifically, the study examines the effect of distributive justice, procedural justice, and interactional justice on five dimensions of organisational citizenship behaviour, namely, altruism, courtesy, conscientiousness, sportsmanship, and civic virtue. As employee perception of organisational justice is likely to affect job satisfaction and leader-member exchange, this study includes these variables as mediators to enrich the understanding of the justice-citizenship relationship. Analysing data drawn from a sample of 267 employees in a range of manufacturing entities using well-established scales, results from principal component analysis and confirmatory factor analysis establish that organisational justice is explained by distributive justice, procedural justice, informational justice, and interpersonal justice while organisational citizenship behaviour is explained by altruism, courtesy, conscientiousness, sportsmanship, and civic virtue. Results of the structural equation modeling analysis reveal that organisational justice partially influences organisational citizenship behaviour, but significantly affects job satisfaction and leader-member exchange. Analysing further, the findings substantiate that job satisfaction has a significant influence on organisational citizenship behaviour while leader-member exchange has a partial effect. When introduced as mediators, the results verify that job satisfaction is indeed an important factor in the justice-citizenship relation. On the contrary, leadermember exchange is not a significant factor in the justice-citizen relationship. The findings provide invaluable implications to theory and practice.